Process Design and Operating Strategies for a Continuous Vaporization System for Purifying Organic Hole‐Transport Materials. Issue 1 (20th November 2018) - Kim, Jin; Park, Kiho; Jin, Seokgeun; Yang, Dae Ryook
Abstract: A continuous vaporization system for the purification of organic hole‐transport materials is proposed to enhance the production rate. A detailed configuration to change a conventional batch process into a continuous one was suggested. The operating strategies of the continuous process were determined from experimental results. Fundamental experiments concerning liquid flow rate through a vertical pipe and product shape were performed. The liquid flow was successfully predicted by using the Hagen‐Poiseuille equation with a correction factor, and a suitable tube design could be estimated to obtain a droplet product. Moreover, an operating temperature window was suggested for uniform shape and size of the final product. This study will be useful for improved process efficiency and successful operation of this process. Abstract : To purify organic hole‐transport materials, the vacuum sublimation/vaporization method is commonly used; however, it has process inefficiency problems, such as limited production and laborious post‐treatment procedures. Therefore, a design upgrade from a batch to a continuous process is proposed to increase the production rate, and operating strategies are suggested.